1981
DOI: 10.1136/gut.22.8.628
|View full text |Cite
|
Sign up to set email alerts
|

Splenic atrophy in adult coeliac disease: is it reversible?

Abstract: SUMMARY A study of splenic function in 28 patients with adult coeliac disease showed no significant correlation between the half life of heat-damaged red cells and either the duration of pre-treatment exposure to gluten or the length of time on a gluten free diet. A significant correlation was found between splenic size and duration of treatment; those patients who had been taking a gluten free diet for the longest time had the smallest spleens. Blood films from 11 of these 28 patients taken before treatment w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…Other investigations have not supported this and have, on the contrary, suggested that splenic hypofunction may be irreversible in adult patients with CD. 114 Hyposplenism appears to be much less common in children with CD, as reported by Corazza et al 115 In their report of 37 children with CD, none were found to have the elevated pitted-erythrocyte count suggestive of hyposplenism. Various autoantibodies including antinuclear antibodies, anti-smooth-muscle antibodies, and antimitochondrial antibodies have been found in patients with CD and hyposplenism.…”
Section: Splenic Dysfunctionmentioning
confidence: 79%
“…Other investigations have not supported this and have, on the contrary, suggested that splenic hypofunction may be irreversible in adult patients with CD. 114 Hyposplenism appears to be much less common in children with CD, as reported by Corazza et al 115 In their report of 37 children with CD, none were found to have the elevated pitted-erythrocyte count suggestive of hyposplenism. Various autoantibodies including antinuclear antibodies, anti-smooth-muscle antibodies, and antimitochondrial antibodies have been found in patients with CD and hyposplenism.…”
Section: Splenic Dysfunctionmentioning
confidence: 79%
“…Hyposplenism appears to be much less common in children with celiac disease [137,142,143,146], with duration of exposure to gluten as a significant factor for the prevalence and severity of the hyposplenism [138]. Adherence to a gluten-free diet was associated with a decrease in pitted red blood cells, suggesting hyposplenism may be reversible [136], but this observation is not supported by other investigators [147]. Higher pitted red blood cell counts were also observed in those with more severe duodenal histology [143] or with complicated celiac disease such as jejunoileitis [140].…”
Section: Hyposplenismmentioning
confidence: 84%
“…Hyposplenism, which may be a complication of chronic folate deficiency, the result of excessive loss of lymphocytes through the damaged GI tract or related to the mucosal lesion [135], is a well-documented complication of celiac disease in historical case series [136][137][138][139][140][141][142][143][144][145][146][147]. Hyposplenism appears to be much less common in children with celiac disease [137,142,143,146], with duration of exposure to gluten as a significant factor for the prevalence and severity of the hyposplenism [138].…”
Section: Hyposplenismmentioning
confidence: 99%
“…Increased sexual activity and satisfaction 263, 264, 268, 274, 275, 277-279, 283, 351 Reduced rates of infertility, miscarriage, intrauterine growth restriction and low birth weight 263, 264, 268, 274, 275, 277-279, 283, 351 Undiagnosed CD may be a risk factor for unfavourable foetal outcome 276 Cardiac disease Improvement in myocarditis and dilated cardiomyopathy 318,355,356 Hyposplenism Functional hyposplenism may be reversible 353 Splenic atrophy usually irreversible 354 …”
Section: Fertility and Reproductionmentioning
confidence: 99%